The Implementation of Disaster Mitigation based on Qur’anic Interpretation: Muhammadiyah Case Study - Danarta, Agung (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2022)
Most Indonesian’s live in vulnerable areas. Various kinds of disasters come alternately with the victims of property and humans. However, there are some people who feel that the disaster is a punishment. This leads to preventive measures or disaster mitigation that are carried out to reduce casualties not to be done, except the appeal not to sin. Muhammadiyah is one of the Islamic organizations that have concerns about disaster mitigation. This research reveals how Muhammadiyah’s perspective on disaster mitigation is. How is the initiation done for the objectivation of mitigation disaster? In addition, see the form of the program carried out as a form of internalization of disaster mitigation in Muhammadiyah. This research is qualitative research using two approaches, namely living Qur’an and phenomenology. The construction of Muhammadiyah’s positive understanding of disasters and disaster mitigation stems from the study of two groups of Qur’anic verses, First, on causality, which is to fully understand why a disaster occurs. Verses studied include az-Zumar (39):9; an-Naml (27):88; Ghafir (41:21). Second, man’s role as caliph governs the universe. Verses studied include az-Zumar (39):18; al-Hashim (59:18); al-Ahzab (33:72); and al-Qasas (28:77). The initiation of disaster mitigation was carried out by Muhammadiyah after the tsunami in Aceh in 2004 and strengthened after the great earthquake in Yogyakarta in 2006. Its main programs are fostering Disaster Resilient Communities, Disaster Safe Schools, and Disaster Safe Hospitals. A positive view of disasters, a friendly attitude with nature based on science. In addition, preventive disaster mitigation measures are the findings of this study. These three attitudes need to be socialized to Indonesian people who live in vulnerable areas.